Analisis Yuridis Putusan Mahkamah Konstitusi Nomor: 56/Puu-Xxi/2023 Tentang Presiden Terpilih Dua Periode Jabatan Tidak Dapat Menjadi Wakil Presiden Periode Berikutnya - Suhada, Muhammad Suhada; Widarto, Joko; Markoni, Markoni; Subiyanto, Achmad Edi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This thesis analyzes the provision that the President-elect for two terms cannot become Vice President for the next term. Where there has been a lawsuit filed with the Constitutional Court to test Law no. 7 of 2011 against the 1945 Constitution filed by the Applicant related to the legal standing in relation to constitutional losses, the Applicant's constitutional rights are potentially harmed in reasonable reasoning that can occur due to the enactment of the norms of Article 169 letter n and Article 227 letter i of Law no. 7 of 2017. Regarding this petition, the Constitutional Court has tried this constitutional case and has decided through decision number 56 / PUU-XXI / 2023. This study uses a normative legal method to examine the provisions on the term of office of the President and Vice President related to the decision of the Constitutional Court. This Constitutional Court decision provides a constitutional interpretation stating that the constitution has provided strict limitations on the term of office of the President and Vice President through Article 7 of the 1945 Constitution which is very important for the implementation of the presidential institution in Indonesia